Teoria de leilões com aplicação ao mercado de petróleo brasileiro - Ferriche, Roberta Coube (2009)
The reform process that the petroleum industry have undergone from the 90 ́s, associated to the transference of public utility services to the private sector, brought important changes to the economy. In this context, the intensified use of auctions, for the privatization of public companies and for the concession of exploration rights assumed a role of great relevance in the Brazilian economy. The discussion on the type of auction used for the sale of oil leases is of great importance, since it represents the beginning of this new policy. Being so, this paper aims at approaching the main aspects that base the choice of an appropriate format of auction, detailing the peculiarities of the oil industry and, finally, analyzing the achieved results.